SEBUAH AGENDA PENELITIAN : MENENTUKAN FAKTOR-FAKTOR YANG MENYEBABKAN PERILAKU KONSUMEN MEMILIH DAN MEMPERGUNAKAN SKUTER MATIK - SETIAWAN, ANDI (STIE Totalwin Semarang, 2011)
This article is a future research agenda for researchers in marketing. This article was formulated on the basis of notes and important facts found in the field. Facts where sales and market share to more extensive automatic scooter. Along with increased sales and increased market share, this article tries to explore further the factors that cause the behavior of consumers choose automatic scooter. It is interesting where the Indonesian market, including market times are difficult to change, efficient and economical image into realms consideration in every decision and became a behavior so far